Update on dermoscopy of Spitz/Reed naevi and management guidelines by the International Dermoscopy Society. (1st September 2017) - Lallas, A.; Apalla, Z.; Ioannides, D.; Lazaridou, E.; Kyrgidis, A.; Broganelli, P.; Alfano, R.; Zalaudek, I.; Argenziano, G.; Bakos, Renato; Blum, Andreas; et al.
Summary: Spitzoid lesions represent a challenging and controversial group of tumours, in terms of clinical recognition, biological behaviour and management strategies. Although Spitz naevi are considered benign tumours, their clinical and dermoscopic morphological overlap with spitzoid melanoma renders the management of spitzoid lesions particularly difficult. The controversy deepens because of the existence of tumours that cannot be safely histopathologically diagnosed as naevi or melanomas (atypical Spitz tumours). The dual objective of the present study was to provide an updated classification on dermoscopy of Spitz naevi, and management recommendations of spitzoid‐looking lesions based on a consensus among experts in the field. After a detailed search of the literature for eligible studies, a data synthesis was performed from 15 studies on dermoscopy of Spitz naevi. Dermoscopically, Spitz naevi are typified by three main patterns: starburst pattern (51%), a pattern of regularly distributed dotted vessels (19%) and globular pattern with reticular depigmentation (17%). A consensus‐based algorithm for the management of spitzoid lesions is proposed. According to it, dermoscopically asymmetric lesions with spitzoid features (both flat/raised and nodular) should be excised to rule out melanoma. Dermoscopically symmetric spitzoid nodules should also be excised or closely monitored, irrespective of age, to rule out atypical Spitz tumours. Dermoscopically symmetric, flat spitzoid lesions should be managed according to the age of the patient. Finally, the histopathological diagnosis of atypical Spitz tumour should warrant wide excision but not a sentinel lymph‐node biopsy.